Validitas E-LKPD Berbasis Strategi KWL (Know-Want-Learned) Pada Materi Ekosistem Untuk Melatih Keterampilan Metakognitif : (Validity of E-LKPD Based on KWL (Know-Want-Learned) Strategy on Ecosystem Material to Train Metacognitive Skills) - Sadikin, Agriani; Dama, Lilan; Husain , Ilyas H.; Mardin, Herinda; Katili, Abubakar Sidik (Program Studi Pendidikan Biologi FKIP Universitas Jambi, 2025)
Biology learning tends to be teacher-centered, resulting in a lack of active student involvement and limited metacognitive skill development. This study aims to determine the validity of the E-LKPD based on the KWL (Know-Want-Learned) strategy on ecosystem material to train students' metacognitive skills. The study used the R&D method with the ADDIE model limited to the Development stage. The research subjects were 18 grade X students of SMA Negeri 6 Gorontalo. Data were collected through teacher interviews and validation by two validators (media and material). The validation results showed that the E-LKPD based on the KWL strategy obtained a